Off like the wind! : the first ride of the pony express - Spradlin, Michael P.; Johnson, Layne (New York : Walker & Co., 2010)
An illustrated history of the Pony Express, the riders carried the mail from Missouri to California, and the dangers they encountered.
Map on endpapers.
School Library Journal, February 2010
Booklist, January 2010
Library Media Connection, January 2010
Includes bibliographical references.
4.4
Keywords: Pony express -- History -- Juvenile literature; Postal service -- United States -- History -- Juvenile literature; West (U.S.) -- History -- 1860-1890 -- Juvenile literature; Pony express -- History; Postal service -- History; West (U.S.) -- History -- 1860-1890.; Pony express -- History; Postal service -- United States -- History; West (U.S.) -- History; Picture books for children